Georgia Architectural and Historic Properties Survey of Quitman [384] 508 W. Screven St., Valdosta, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Quitman [384] 508 W. Screven St., Valdosta, Ga. December 1980. The Bentley House. Rectangular plan house. Multi-gabled roof. Square porch posts. Gingerbread trim. Clapboard siding. Sash windows with 9/9 lights. Transom and sidelights. Set on brick piers. Double doors. Good condition. Date of Construction: c. 1865. Significant as part of a potential National Register historic district, along Screven St., and north and south of it, and including the commercial area.
1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.25 MB (1,311,683 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Quitman (Ga.)